2023
DOI: 10.1007/s44169-023-00035-z
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Biofilm Formation on the Physicochemical Properties and Toxicity of Microplastics: A Concise Review

Joshua Moyal,
Preeti H. Dave,
Mengjie Wu
et al.

Abstract: Microplastics (MPs) are of global concern due to their slow degradation in the environment and the potential of inducing adverse effects on organisms. In aquatic ecosystems, microbes routinely colonize MPs and develop biofilms on their surfaces. Biofilms are assemblages of surface-associated microbial cells that are enclosed in an extracellular polymeric substance. Emerging evidence has suggested that the development of biofilm can alter the physicochemical properties and the pollutant adsorption capability on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 206 publications
0
4
0
Order By: Relevance
“…In secondary treatment, microbes adhere to MP surfaces, secrete extracellular polymeric substances (EPSs), colonize the surface, and replicate to create biofilms [60]. This process disrupts microbial communities and interferes with biological treatment processes.…”
Section: Impact Of Mps On Wastewater Treatmentmentioning
confidence: 99%
“…In secondary treatment, microbes adhere to MP surfaces, secrete extracellular polymeric substances (EPSs), colonize the surface, and replicate to create biofilms [60]. This process disrupts microbial communities and interferes with biological treatment processes.…”
Section: Impact Of Mps On Wastewater Treatmentmentioning
confidence: 99%
“…Because MPs are small and lightweight, they can act as vectors for microorganisms, facilitating the long-distance transport, especially in aquatic environments, which are susceptible to wind flows and water currents (Sun et al 2021 ; Sooriyakumar et al 2022 ). This introduces microorganisms attached to the MPs surface into new potential habitats, posing environmental and public health risks if biofilms harbor human and animal pathogens and/or invasive species (Frère et al 2018 ; Delacuvellerie et al 2022 ; Sooriyakumar et al 2022 ; Moyal et al 2023 ). Additionally, MPs can serve as active hotspots for horizontal gene transfer (HGT), i.e.…”
Section: Microbial Biofilms On Microplasticsmentioning
confidence: 99%
“…While HGT can occur naturally, MPs biofilms provide favorable conditions for genetic information transmission, with a high density of bacterial cells in a confined space and an active metabolic activity (Wang et al 2023 ). This can significantly increase the transfer of resistance genes, including those for heavy metals and antibiotics (Sun et al 2021 ; Laganà et al 2019 ; Moyal et al 2023 ). Particularly concerning is antibiotic resistance, attributed to the release of antibiotics into the environment and promotes the development of resistance in bacteria colonizing MPs (Atugoda et al 2020 ).…”
Section: Microbial Biofilms On Microplasticsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this result is controversial, as some studies have indicated a decrease in microbial diversity with biofilm development [38,39], while others reported increased diversity in the presence of PS [40][41][42]. This discrepancy could be attributed to the "umbrella effect" of MPs on the survival and growth of microorganisms in wastewater, but their effects seem to be influenced by the chemical and physical properties of MPs, as well as environmental conditions [43][44][45]. It is plausible that the formation of an extracellular polymeric substance (EPS) plays a crucial role in the formation, stability, and functioning of microcolonies on the PS.…”
Section: Bacterial Community Diversity and Clusteringmentioning
confidence: 99%